Wide gap Chern Mott insulating phases achieved by design - Hongli Guo (Nature Portfolio, 2017)
Condensed Matter Physics: quantised Hall transport in two dimensional magnetic insulators Simulations predict a Chern insulating state with quantized anomalous Hall transport in insulators without an applied magnetic field. These strongly correlated systems are designed based on transition metal oxides, unlike existing weakly correlated electron-based examples whose bulk conduction masks surface currents. An international team led by Warren Pickett at the University of California Davis designed the materials based on a buckled honeycomb lattice. By tuning spin, orbital, charge, and lattice degrees of freedom as well as strain, they predict robust ruthenium and osmium bilayers with conducting boundary states, while retaining a bulk bandgap of up to 130 meV. These properties, topologically protected by electronic entanglement, provide promise of applications in next generation electronics and possibly quantum computing. These systems offer more robust platforms than previously suggested and guide experimental synthesis to exploit these emergent phenomena.